2016
DOI: 10.5897/ajmr2016.7917
|View full text |Cite
|
Sign up to set email alerts
|

An overview of food safety knowledge and practices in selected schools in the city of Al Ain, United Arab Emirates

Abstract: Safe food handling in school canteens is an important practice to protect the students from food borne illnesses. The main purpose of this study was to present an overview of food safety knowledge and hygienic practices in selected schools in Al Ain city in the Emirate of Abu Dhabi, United Arab Emirates. The study consisted of three parts. The first part tackled students' and teachers' behavior during breakfast snack in addition to a quick assessment of premises from a food safety point of view. The second par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…A selected group of early-schoolaged Polish children showed high accuracy in this area, as most of them declared use soap for washing and a towel or dryer for drying. The values obtained are comparable to the other results: 84% of the respondents said they use water and soap to wash their hands (Abushelaibi et al, 2016). Głąbska et al (2020) concluded that during the COVID-19 pandemic, all the assessed hand hygiene behaviors of Polish adolescents were satisfying, but the authors emphasized that hand hygiene education is still necessary.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…A selected group of early-schoolaged Polish children showed high accuracy in this area, as most of them declared use soap for washing and a towel or dryer for drying. The values obtained are comparable to the other results: 84% of the respondents said they use water and soap to wash their hands (Abushelaibi et al, 2016). Głąbska et al (2020) concluded that during the COVID-19 pandemic, all the assessed hand hygiene behaviors of Polish adolescents were satisfying, but the authors emphasized that hand hygiene education is still necessary.…”
Section: Discussionsupporting
confidence: 71%
“…School children's hands are a reservoir of many microorganisms, and many authors have confirmed their presence on pupil's hands. One such microorganism is Escherichia coli (Randle et al, 2013;Abushelaibi et al, 2016), which may indicate fecal contamination because of poor hygiene after using the toilet (Curtis and Cairncross, 2003). Good hand hygiene is an important way to eliminate current pathogens from the surfaces of hands and is an effective way to fight against infection, both at home and in the food plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study carried out in 2016 in the Ashanti region of Ghana, showed that 52% of the 180 students assessed, who ate more of their meals at school time, had FBD between 3 and 12 times per academic year (Ababio et al, 2016b). In Germany, one of the largest bouts of gastroenteritis in 2012 came from contaminated food in schools, compromising the health of 11,200 students (Aisha et al, 2016). In Brazil, this scenario is no different because, according to the Ministry of Health's Health Surveillance Secretariat, of the 12,503 FBD outbreaks that occurred between 2000 and 2017, 8.6% occurred in the school environment .…”
Section: Introductionmentioning
confidence: 99%